Motorcycles are more prone to road accident in Malaysia: with special reference to moped accidents / Wan Zaiyana Mohd Yusof - Mohd Yusof, Wan Zaiyana (1997)
Crash injury investigation is by nature a highly complex activity which no formal academic training can cover the full spectrum and there are relatively few skilled practitioners in existence.